2020
DOI: 10.5530/fra.2020.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Preservation of Total Phenolic Content and Antioxidant Activity in Extra Virgin Olive Oil: A Physico-biochemical Approach

Abstract: Objectives: This work, on low-cost controlled freeze methodology for stabilizing the phenolic content in Extra Virgin Olive Oil (EVOO), is evaluated by studying four Quality Indexes (QIs): free acidity, as % of oleic acid (1 st-QI); UV-absorption values; K 272 , K 232 and ΔK (2 nd-QI); total phenolic content (TPC), as Gallic acid equivalence (3 rd-QI); and lipid peroxidation products, as free malondialdehyde (MDA) (4 th-QI). Methods: The study of QIs for EVOO under storage, absence of light, at 25, 4,-20 and-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…(iv) Additionally, at production and irrespective of the ±N 2 purge and temperature, it attains a minimum PV LOOH value of ∼6 mEql/kg, which is ∼3-fold lower than the allowable EE minimum value of 20 mEql/kg. These data are also in agreement with a previous study that found that oxidation delay of EVOO from the same Koroneiki monovariety can be achieved by minimally storing it in a cool and dark place . It should also be noted that EVOO oxidation of the same variety has been studied in other areas in Greece and measured by the traditional PV IT test (ranging from 6.20 to 74 mEql O 2 /kg). …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…(iv) Additionally, at production and irrespective of the ±N 2 purge and temperature, it attains a minimum PV LOOH value of ∼6 mEql/kg, which is ∼3-fold lower than the allowable EE minimum value of 20 mEql/kg. These data are also in agreement with a previous study that found that oxidation delay of EVOO from the same Koroneiki monovariety can be achieved by minimally storing it in a cool and dark place . It should also be noted that EVOO oxidation of the same variety has been studied in other areas in Greece and measured by the traditional PV IT test (ranging from 6.20 to 74 mEql O 2 /kg). …”
Section: Resultssupporting
confidence: 91%
“…These data are also in agreement with a previous study that found that oxidation delay of EVOO from the same Koroneiki monovariety can be achieved by minimally storing it in a cool and dark place. 20 It should also be noted that EVOO oxidation of the same variety has been studied in other areas in Greece and measured by the traditional PV IT test (ranging from 6.20 to 74 mEql O 2 /kg). 21−24 3.1.3.…”
Section: Long-term Preservation Evaluation Of Evoo By the Pv Looh Testmentioning
confidence: 98%
“…Unsaturated fatty acids are the intrinsic reason for lipid oxidation 26 . c9511_g1 and c9756_g1 , encoding fatty acid synthase were downregulated in the High OA group compared to that of the control group, which suggests that lipid oxidation is lower in the High OA group.…”
Section: Discussionmentioning
confidence: 99%
“…This trend is probably due to the hydrolytic and oxidative degradation processes of main secoiridois (oleuropein, oleacin, oleocanthal, 3,4-DHPEA-EA, and p-HPEA-EA) [40,41], which in fact decreased significantly under all conditions. It is widely recognized that tyrosol and hydroxytyrosol typically increase in aged EVOOs [6,9,15,16,42] and, considering that hydroxytyrosol represents an important bioactive compound for human health, with a strong antioxidant activity [43,44], a low concentration of this molecule, when balanced by a high concentration of complex phenols, may represent a good compromise for EVOOs from a quality standpoint. The relationship between complex and simple phenolic compounds also depends on the initial content and processing conditions [5,45,46].…”
Section: Phenolic Compoundsmentioning
confidence: 99%